Expression and clinical significance of latent-transforming growth factor beta-binding protein 2 in primary hepatocellular carcinoma. Issue 39 (September 2019) - Chen, Jinchun; Gao, Guosheng; Wang, Hui; Ye, Xingtao; Zhou, Jun; Lin, Jianjun
Abstract : Abstract: The present study aimed to explore the expression of latent transforming growth factor β binding protein 2 (LTBP2) in patients with hepatocellular carcinoma (HCC) and their correlation to clinicopathologial features. Serum levels of LTBP2 in 60 patients with HCC, 35 patients with hepatocellular benign tumors, 60 patients with precancerous lesions of HCC, and 60 healthy volunteers were determined by enzyme-linked immunosorbent assay. The expression levels of LTBP2 at messenger RNA (mRNA) and protein levels in 60 cases of HCC and adjacent tissues were detected by quantitative real-time polymerase chain reaction and immunohisochemistry. Statistical analysis was used to analyze the relationship between LTBP2 and clinical characteristics of patients with HCC. The mRNA and protein levels of LTBP2 were significantly upregulated in HCC tissues compared to adjacent tissues. Additionally, higher serum LTBP2 level was also observed in HCC patients relative to normal controls. Further investigation demonstrated that LTBP2 expression was associated with malignant degree of tumor, tumor progression, tumor differentiation, tumor size, tumor stage and hepatitis virus infection, and has prognostic implications in HCC patients. LTBP2 might be served as a potential biomarker in diagnosis and treatment of HCC. Abstract : Supplemental Digital Content is available in the text